Evaluation of microencapsulated diets for tropical gar (Atractosteus tropicus) larviculture - Saenz de Rodrigáñez, Miguel (2018)
Four microencapsulated diets were evaluated with respect to the growth and survival of tropical gar Atractosteus tropicus larvae. The treatments consisted of four experimental diets and one control diet 1) fish meal, 2) a combination of pork and poultry meals, 3) Nannochloropsis gaditana meal, 4) enzyme preparation and the control treatment 5) Artemia nauplii. The evaluation indicated that the larvae fed the Artemia nauplii obtained the greatest growth and survival (3.93 cm, 0.19 g y 82 % respectively), which justifies a correct culture system operation. While larvae fed microencapsulated diets best values in survival were observed with diets Nannochloropsis gaditana and enzyme preparation (20.0 and 19.2 %). Our results showed that microencapsulated could be used to feed A. tropicus in feasibly form. However, more information concerning to optimize the design and manufacturing are required to improve the growth and survival of organisms.